THE CONCEPT OF LEADERSHIP IN NAMO BAIKOLE: ANTOLOGI CERITA RAKYAT TIDORE (A STUDY IN SOCIOLOGY OF LITERATURE) - Kurniawan, Roni; Sisvareza, Damaz Aristy; Kusumaningtyas, Adityarini (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2023)
Literature, including folk literature, are reflections of imaginations, beliefs, knowledge, and experiences of the creators. Literature manuscripts provide a wealth of information about the lives of people who lived in the past, including leadership style, politics, social life, economy, religion, culture, and language. Some of folklore in Tidore is documented in an anthology called “Namo Baikole: Antologi Cerita Rakyat Tidore” that contains 7 local traditional stories. The aim of the study is to find the concept of leadership in the anthology. The method used in this research is descriptive qualitative and uses content analysis. The data collection technique in this research is document analysis using a literary sociology approach or study. The literary sociology applied in this research is literary sociology in the framework of understanding social ideas regarding the concept of leadership contained in Namo Baikole: Antologi Cerita Rakyat Tidore. The result shows that there are three leadership concepts described in the “Namo Baikole: Antologi Cerita Rakyat Tidore” book, namely leaders must be wise in making decisions, leaders must be brave and be able to solve problems, and leaders must be smart or intelligent.